Resilience among vulnerable households in Europe: Questions, concept, findings and implications - Markus Promberger (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
The paper shows the results of the RESCuE project, an in-depth qualitative investigation of 250 vulnerable households, their living conditions and socioeconomic practices across nine European countries on the background of the European crisis since 2008. After refining the concept and developing an analytical framework, three major findings are in the focus: First, the concept of resilience proves to be useful and transferable into poverty and social policy research under certain prerequisites. Second, a wide scope of interrelated, substitutable and polyvalent practices allows the very few resilient households to gain their livelihood from mixed sources. Among some of them, direct transfer incomes play only a minor role. Third, there is a surprising high relevance of common goods for low income households. Moreover, certain cultural patterns of knowledge and values, and personal networks also play a crucial role for some doing better than other vulnerable households. Policy implications include first the continuing need for the welfare state, as resilience is vulnerable itself. Second, social policy needs to care for common goods of a considerable scope, available for all citizens, but mostly needed by those living on low income. – – Das Papier berichtet die Ergebnisse des Projektes RESCuE, einer vertieft angelegten qualitativen Studie in 250 vulnerablen Haushalten in neun europäischen Ländern vor dem Hintergrund der europaweiten Krise seit 2008. Nach der Verfeinerung des Resilienzkonzeptes und der Entwicklung eines analytischen Rahmens stehen vier wichtige Befunde im Fokus: Erstens, Nutzen und Übertragbarkeit des Konzeptes in Armuts- und Sozialpolitikforschung. Zweitens konnte in den wenigen anzutreffenden resilienten Haushalten ein weites Spektrum von gegenseitig substituierbaren, miteinander verwobenen und polyvalenten Praktiken identifiziert werden, mittels denen ein Lebensunterhalt aus gemischten Quellen erwirtschaftet wird. Direkte Transfereinkommen spielen, zumindest für manche Typen resilienter Haushalte, dabei eine vergleichsweise geringe Rolle. Dies wird drittens unter anderem ausgeglichen durch die hohe Bedeutung und Nutzung von Kollektiv- und Gemeingütern. Hinzu kommen Kulturmuster und Netzwerkbeziehungen, die es den Betroffenen erlauben, mit ihrer Lage besser zurechtzukommen als andere. Für die Sozialpolitik bedeutsam ist erstens die Notwendigkeit der Aufrechterhaltung oder Schaffung eines leistungsfähigen Wohlfahrtstaates, denn Resilienz von Niedrigeinkommenshaushalten ist oft genug instabil und vulnerabel. Zweitens zeigt sich deutlich die Notwendigkeit eines umfangreichen Spektrums von Gemeingütern, die im Prinzip allen Bürgern zur Verfügung stehen, jedoch vor allem Niedrigeinkommensbeziehern das Leben erleichtern können.
Keywords: I30; Z13; 330; Resilience; Poverty; Social Policy; Households; Economy of private Households